2008
DOI: 10.1002/ibd.20310
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of inflammatory bowel disease in the Songpa-Kangdong district, Seoul, Korea, 1986–2005: A KASID study

Abstract: The incidence and prevalence of CD and UC in Seoul, Korea, are still low compared with those in Western countries, but are rapidly increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
298
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 431 publications
(339 citation statements)
references
References 48 publications
27
298
7
Order By: Relevance
“…This survey investigated the approximate annual number of patients treated in each institution, and does not accurately reflect the incidence and prevalence of IBD in each country. However, marked increases have been reported in the incidence and prevalence of IBD over the last 10-20 years in Japan, Korea and China, suggesting that the results of this survey are consistent with the actual situation [17,18,19,20]. Consistent with previous studies, there are generally more UC than CD patients in the East Asian countries surveyed [1].…”
Section: Discussionsupporting
confidence: 80%
“…This survey investigated the approximate annual number of patients treated in each institution, and does not accurately reflect the incidence and prevalence of IBD in each country. However, marked increases have been reported in the incidence and prevalence of IBD over the last 10-20 years in Japan, Korea and China, suggesting that the results of this survey are consistent with the actual situation [17,18,19,20]. Consistent with previous studies, there are generally more UC than CD patients in the East Asian countries surveyed [1].…”
Section: Discussionsupporting
confidence: 80%
“…Korea and other East Asian countries, once considered being a region in which IBD was extremely rare, have had a rapidly increasing number of patients with IBD. The population-based Korean data showed that the mean annual incidence rates of Crohn's disease (CD) and ulcerative colitis (UC) increased from 0.05 and 0.34 per 100000 persons, respectively, in 1986-1990 to 1.34 and 3.08 per 100000, respectively, in 2001-2005 [2] . Anti-TNF agents such as infliximab and adalimumab have been used with gradually increasing frequency since they were approved for IBD treatment in the mid 2000s in Korea [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Because appendectomy is a reported risk factor for CD, the exclusion of patients with a history of appendectomy raises the possibility that some patients with a spontaneous perforation due to CD may have also been excluded. However, considering that the annual incidence of CD in Korea is 1.34/100,000, the possibility of a spontaneous perforation due to CD in cases with a history of appendectomy is thought to be very low [13]. Consequently, it is speculated that excluding those with a medical history of abdominal surgery did not significantly impact the results of our study.…”
Section: Discussionmentioning
confidence: 41%
“…Recently, it was reported that the incidence of inflammatory bowel diseases such as CD and ulcerative colitis is increasing in South Korea [13]. Another recent report showed that the incidence of small-bowel perforation due to typhoid enteritis decreased from 70% in 1984 to 14% in 2003, but the incidence of perforation due to CD increased from 0% in 1984 to 14% in 2003 [14].…”
Section: Discussionmentioning
confidence: 99%